Improvement of quality of logistical service of the cargo terminal - Шраменко, Наталя Юріївна (Eastern-European Journal of Enterprise Technologies, 2012)
Consider the modern requirements to the terminal system of delivery. Detected range of services and the expediency of providing them to the cargo terminal to improve the quality of logistic service.